Natural Killer Cell Adoptive Transfer Therapy: Exploiting the First Line of Defense Against Cancer. Issue 6 (November 2015) - Davis, Zachary B.; Felices, Martin; Verneris, Michael R.; Miller, Jeffrey S.
Abstract : Abstract: Natural killer (NK) cells constitute an important component of the initial immunological response against transformed cells. However, chronic exposure to the tumor microenvironment can fundamentally alter the ability of NK cells to sufficiently control tumor progression. Thus, the adoptive transfer of healthy, functional NK cells as an interventional therapy has been an area of great interest for improving patient outcomes. Recent developments in the field have provided a better understanding of what makes the NK compartment effective against malignant cells. Moreover, there are now multiple potential sources of NK cell products for infusion as well as techniques to manipulate these cells to enhance their antitumor functions. This review explores the advantages and disadvantages of various sources of NK cells as well as prospective therapeutic enhancements to adoptively transferred NK cells.